Increased Expression Levels of Apoptosis Inhibitor BIRC5 Is Associated with Advanced Oropharyngeal Squamous Cell Carcinoma. (23rd August 2013) - Janus, Jeffrey R.; Laborde, Rebecca R.; Moore, Eric J.; Olsen, Kerry D.; Olsen, Steven; Kasperbauer, Jan L.; Smith, David
Abstract : Objectives: 1) Describe the role that BIRC5 and related activator genes (AURKB and CDCA8) play in various malignancies, and analyze the role that these genes play in oropharyngeal squamous cell carcinoma. 2) Implement innovative gene analysis technology (mRNA Seq) to determine gene expression and validate using established techniques (nCounter). 3) Analyze gene expression in the setting of human papillomavirus (HPV) status, smoking, and tumor stage. Methods: Tumor and adjacent normal oropharyngeal mucosal samples were obtained for validation studies from 24 patients undergoing surgical treatment of oropharyngeal squamous cell carcinoma (OPSCC) from 2010‐2012. Transcriptome data (mRNA‐Seq) were analyzed from patient matched tumor‐normal tissues. Transcript levels of target genes were validated using the nCounter system. Expression levels were correlated with tumor stage, HPV infection status, or smoking status. Results: A statistically significant overexpression was noted in all 3 target genes in tumor versus normal tissue. Statistically significant associations were present between expression levels of target genes and advanced tumor stage. No significant association was found between the 3 genes and etiologic subgroupings (HPV latent versus active infections or smoking status). Conclusions: BIRC5 and related activator genes (AURKB and CDCA8) have an established role in the development and progression of other cancers. Expression of these 3 gene targets is related to tumor stage in oropharyngeal SCC. The significant associations between the expression of these genes and tumor staging suggest that these genes may play a role in tumor progression independent of HPV viral expression patterns.